Memory Modulation: Ethical Issues and Identity-Broadening - Lavazza, Andrea (Filosofia Morale/Moral Philosophy, 2024)
The human desire to erase negative memories is as old as civilization itself, mirroring our long-standing aspiration to enhance our memory. While the latter goal has been partially achieved without significant ethical concerns, the former has remained elusive. Recent scientific advancements, however, have opened the possibility of manipulating memories to mitigate their emotional impact and potentially remove certain mnemonic traces. This raises several ethical quandaries that form the focus of this paper. The inquiry extends beyond the moral implications of memory erasure to examine the concept of personal identity, which is deeply rooted in memory and may become less rigid and persistent in light of these emerging memory manipulation techniques.